Equalisasi PPN atas Penjualan Ekspor dan Implikasinya terhadap Laba Sebelum Pajak PT X Tahun 2025 - Nuer Aisa; Dwi Anggarani; Khojanah Hasan; Zaenuddin Zaenuddin (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study analyzes the impact of differences in the recognition of export sales transactions on the determination of net profit before tax at PT X. Descriptive qualitative method is used to examine in depth the difference in export sales value between accounting standards and tax regulations. Data collection was carried out through observation techniques, interviews as well as documentation of financial statements and export sales documents. The analysis focuses on the implications of the difference between the Bill of Lading reference document and the PEB and the use of the foreign exchange conversion rate between the Central Exchange Rate of Bank Indonesia and the Minister of Finance Rate. The results of the study show that there is a nominal difference in export sales between the profit and loss statement and the VAT return. The use of accounting data results in a greater net profit value compared to the tax reference. This study concludes that proper and periodic reconciliation of export sales is very important to minimize the risk of fiscal differences and ensure the accuracy of the company's financial statements.